Brucella infection in a dairy herd of Chattogram, Bangladesh - F. M. Yasir Hasib; Md. Sirazul Islam; Chandan Nath; Md. Moktadir Billah Reza; Md. Masuduzzaman; Sharmin Chowdhury (Veterinary Research Notes)
Objective: This study aimed to confirm probable causes of abortion with subsequent characterization of Brucella isolates from a dairy herd in the Chattogram district of Bangladesh. Materials and Methods: This study was conducted on a dairy herd of 137 cattle in which two abortions were experienced within days. Samples comprising aborted fetal tissues, uterine fluid, placental cotyledon, and whole blood were collected and processed to determine the cause of abortions. Serum samples (n = 137) were tested by Rose Bengal plate test (RBPT) and Indirect Enzyme Linked Immunosorbent Assay (I-ELISA). Isolation and identification were performed following standard bacteriological and molecular techniques. Results: A total of 91 samples (66.42%, 95% CI: 58.15–73.80) and 101 samples (73.72%, 95% CI: 65.75–80.40) tested positive by RBPT and I-ELISA, respectively. Both of the aborted samples were positive based on culture characteristics, RBPT, and I-ELISA tests, and were further confirmed as Brucella abortus through the AMOS-PCR assay. Partial genome sequencing of the two polymerase chain reaction-positive samples, followed by phylogenetic analysis, revealed close similarity with isolates from India, Pakistan, and China. Conclusion: The culling of brucellosis-positive cattle is the key to controlling and preventing brucellosis in herds. The findings highlighted the importance of brucellosis screening for optimizing both herd health and public health. [Vet. Res. Notes 2025; 5(7.000): 55-60]